2021
DOI: 10.3758/s13423-021-01927-8
|View full text |Cite
|
Sign up to set email alerts
|

A pre-registered, multi-lab non-replication of the action-sentence compatibility effect (ACE)

Abstract: The Action-sentence Compatibility Effect (ACE) is a well-known demonstration of the role of motor activity in the comprehension of language. Participants are asked to make sensibility judgments on sentences by producing movements toward the body or away from the body. The ACE is the finding that movements are faster when the direction of the movement (e.g., toward) matches the direction of the action in the to-be-judged sentence (e.g., Art gave you the pen describes action toward you). We report on a pre-regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…To create the two shape conditions (match/mismatch), each one of the sentences in each pair was matched with the two pictures depicting the verbally described object in two different 1 The SPV task (Zwaan et al, 2002) was chosen because, as opposed to other simulation-inducing paradigms (e.g., Morey et al, 2021), this paradigm has been wellestablished in terms of producing the visual shape effect in the L1. Indeed, this effect has been replicated in numerous L1 studies (e.g., De Koning, Wassenburg, Bos & van der Schoot, 2017b;Engelen, Bouwmeester, De Bruin & Zwaan, 2011;Hirschfeld, Zwitserlood & Dobel, 2011), including studies examining L1-Hebrew (Peleg et al, 2018) and L1-English (e.g., Zwaan & Madden, 2006;Zwaan & Pecher, 2012), the two languages that were tested in the current study, ruling out the possibility that the shape effect would be modulated by the specific language (Hebrew/English) rather than by the nativeness of language (L1/L2) as was intended.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To create the two shape conditions (match/mismatch), each one of the sentences in each pair was matched with the two pictures depicting the verbally described object in two different 1 The SPV task (Zwaan et al, 2002) was chosen because, as opposed to other simulation-inducing paradigms (e.g., Morey et al, 2021), this paradigm has been wellestablished in terms of producing the visual shape effect in the L1. Indeed, this effect has been replicated in numerous L1 studies (e.g., De Koning, Wassenburg, Bos & van der Schoot, 2017b;Engelen, Bouwmeester, De Bruin & Zwaan, 2011;Hirschfeld, Zwitserlood & Dobel, 2011), including studies examining L1-Hebrew (Peleg et al, 2018) and L1-English (e.g., Zwaan & Madden, 2006;Zwaan & Pecher, 2012), the two languages that were tested in the current study, ruling out the possibility that the shape effect would be modulated by the specific language (Hebrew/English) rather than by the nativeness of language (L1/L2) as was intended.…”
Section: Methodsmentioning
confidence: 99%
“…Growing up, they keep using their native language and experiencing the world simultaneously and constantly, and thus, their neural networks associated with L1 processing and those associated with the processing of real-life experiences become strongly linked over time. Therefore, as mentioned above, L1 users routinely simulate perceptual (e.g., Brunyé, Ditman, Mahoney, Walters & Taylor, 2010; Zwaan et al, 2002), motor (e.g., Glenberg & Kaschak, 2002; Myung, Blumstein & Sedivy, 2006; Scorolli & Borghi, 2007), and affective (e.g., Havas, Glenberg & Rinck, 2007; Niedenthal, Winkielman, Mondillon & Vermeulen, 2009) knowledge during language comprehension (but see Bedny & Caramazza, 2011; and Mahon, 2015, for an alternative view; and also Morey, Kaschak, Díez-Álamo, Glenberg, Zwaan, Lakens, Ibáñez, García, Gianelli, Jones, Madden, Alifano, Bergen, Bloxsom, Bub, Cai, Chartier, Chatterjee, Conwell, Cook, Davis, Evers, Girard, Harter, Hartung, Herrera, Huettig, Humphries, Juanchich, Kühne, Lu, Lynes, Masson, Ostarek, Pessers, Reglin, Steegen, Thiessen, Thomas, Trott, Vandekerckhove, Vanpaemel, Vlachou, Williams & Ziv-Crispel, 2021, for a failure to replicate the action-sentence compatibility effect first reported by Glenberg & Kaschak, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies failed to find such effects or found only tiny ones. Moreover, the direction of these effects was often unpredictable (e.g., Estes & Barsalou, 2018;Morey et al, 2021;Shebani & Pulvermüller, 2018). With substantial evidence that sensory and motor simulations contribute to language processing, research questions are now shifting to how these embodied effects translate to situated, real-world language processing and comprehension (e.g., Barsalou, 2019;García & Ibáñez, 2016a;Hasson, Egidi, Marelli, & Willems, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Psychology is finally finding black swans. A number of prominent theories have been called into question including ego depletion [22], the action-sentence compatibility effect [23], frontal asymmetry as a marker for depression [24], the growth mindset [25], and various priming effects [26,27]. In the absence of these refutations, progress in psychology was stagnant as researchers considered these (incorrect) theories as proven.…”
Section: Why Losing Is Better Than Winning (In Science)mentioning
confidence: 99%